Design of Slip Horizontal Table System For Shaker - Ömer Kadir Morgül (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Shakers can produce vibration functions atthe desired frequencies and amplitudes according to the vibration standards.Also, shakers have the same working principle with devices of hydraulic,mechanical pneumatic, electromagnetic etc. Shakers can produce vibration in thevertical and horizontal direction depending on the type of table. The testsample was fixed on the table with fixture. In this study, the appropriate slipetable was designed and manufactured in order to improve test capability ofshaker. Thereforeshaker had the capability of vibration drive in the horizontal directions fortest sample. Finite element method (FEM), modal analysis,harmonic analysis and vibration measurements were applied to assess vibrationanalysis. After, results of FEM and confirmation experimental were in a good agreementwith each other, the design of vibration shaker table system was manufactured.